Role of Nanotechnology and Their Perspectives in the Treatment of Kidney Diseases - Merlin, J. P. Jose; Li, Xiaogang (Frontiers in Genetics, 2022)
Nanoparticles (NPs) are differing in particle size, charge, shape, and compatibility of targeting ligands, which are linked to improved pharmacologic characteristics, targetability, and bioavailability. Researchers are now tasked with developing a solution for enhanced renal treatment that is free of side effects and delivers the medicine to the active spot. A growing number of nano-based medication delivery devices are being used to treat renal disorders. Kidney disease management and treatment are currently causing a substantial global burden. Renal problems are multistep processes involving the accumulation of a wide range of molecular and genetic alterations that have been related to a variety of kidney diseases. Renal filtration is a key channel for drug elimination in the kidney, as well as a burgeoning topic of nanomedicine. Although the use of nanotechnology in the treatment of renal illnesses is still in its early phases, it offers a lot of potentials. In this review, we summarized the properties of the kidney and characteristics of drug delivery systems, which affect a drug’s ability should focus on the kidney and highlight the possibilities, problems, and opportunities.